2000
DOI: 10.1175/1520-0469(2000)057<2684:eoaoca>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aerosols on Cloud Albedo: Evaluation of Twomey’s Parameterization of Cloud Susceptibility Using Measurements of Ship Tracks

Abstract: Airborne measurements from the Meteorological Research Flight's Hercules C-130 and the University of Washington's Convair C-131A during the Monterey Area Ship Track field project are used to evaluate Twomey's analytic expression for cloud susceptibility, which describes the sensitivity of cloud albedo to changes in droplet concentrations. This expression incorporates assumptions about cloud physics, such as the independence of the cloud liquid water content and the width of the droplet size distribution on dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
147
3
8

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(170 citation statements)
references
References 28 publications
(53 reference statements)
12
147
3
8
Order By: Relevance
“…1). Studies of shiptracks (27) have shown satisfactory agreement with ⌬␣ c and report a weak correlation between lwc and n D which removes the 2⌬lwc/lwc Ϫ1 and 3⌬h/h term in Eq. 3.…”
Section: Resultsmentioning
confidence: 93%
“…1). Studies of shiptracks (27) have shown satisfactory agreement with ⌬␣ c and report a weak correlation between lwc and n D which removes the 2⌬lwc/lwc Ϫ1 and 3⌬h/h term in Eq. 3.…”
Section: Resultsmentioning
confidence: 93%
“…In addition to the RF mechanisms considered in this study, other indirect processes have been proposed. These include reduction of snow and ice albedo by BC deposition (38)(39)(40), the so-called semidirect effect of BC on clouds (41), and indirect effects on cirrus clouds by particles from aviation (8). These RF mechanisms are generally given a low or very low level of scientific understanding by the IPCC (34).…”
Section: Discussionmentioning
confidence: 99%
“…For example, for a case study over the North Sea, where f rain D 0.2 N \ 100 cm~3 (Nicholls 1984), while in California stratocumulus it increased from 0.3 to 0.5 as N decreased from 40 cm~3 in clouds contaminated by ship exhaust to 10 cm~3 in clean ambient air (from Fig. 3b of Ackerman et al 2000b). We note that in clean marine stratocumulus, reduced rain is observed (e.g., Taylor & Ackerman 1999) and predicted (e.g., Ackerman, Toon, & Hobbs 1993 ;Stevens et al 1998) to result in deeper cloud layers, which is consistent with our simple model.…”
Section: The Present Modelmentioning
confidence: 99%